Pendampingan Inovasi Olahan Es Krim Jahe-Kencur pada Kelompok Wanita Tani di Mangliawan Malang - Nour Athiroh; Nurul Jadid Mubarakati (Universitas Islam Nahdlatul Ulama Jepara, 2020)
Ginger and galangal powder are less attractive to people in Mangliawan village. The cooperative's ginger powder sales business experienced a setback. The aim is to provide creativity and innovation assistance to this ginger powder as a raw material for ice cream. The phenomenon of this decade appears in various variants of ice cream, but there is no ginger-galangal based ice cream business yet. The service method consists of: 1) program socialization, 2) training in making ice cream, 3) formation of non-governmental organizations as program partners, 4) program monitoring, 5) focus group discussion, f) evaluation. Measurement of the impact of the activity was carried out using a questionnaire technique which aims to obtain a direct picture of the community in Mangliawan village. The results of the service program are 1) the public's knowledge of the potential of kencur ginger and its processing has increased; 2) Partners know how to make kencur ginger ice cream; 3) public knowledge of the benefits of ginger ice cream increases; 4) There is a desire of the respondent to open a ginger-kencur ice cream business plan and increase the economic level.